Convex Combination Method on Probabilistic Fuzzy Multiobjective Transportation Problem with Pareto Distribution - Eka Susanti; Oki Dwipurwani; Novi Rustiana Dewi; Indrawati Indrawati; Indri Yune Safira (JINAV: Journal of Information and Visualization, 2022)
This article introduces a transportation model with two objective functions. The first objective function is the function which minimizes the total cost and the second objective function is the function which minimizes the total time. Parameters of source, destination and maximum capacity of transportation means are assumed to follow the Pareto distribution. The multiobjective transportation model is the development of a single objective transportation model. Parameters of the objective function are expressed by triangular fuzzy numbers. Fuzzy multi objective problems are transformed into a deterministic single objective using the convex combination method. The formulated model is applied to the problem of shipping metal crates. There are 3 types of conveyances namely HDL, Engkel and Wingbox. Obtained the optimal total cost of Rp. 3,770,294 and metal crates delivery time to be for 13 hours.